Teachers’ metacognition and Higher Order Thinking Skills (HOTs) of Elementary School learners in Eastern Samar, Philippines - Princess Mae M Ellado (Center for Humanities and Innovation Studies, 2021)
This investigation aimed to identify a significant relationship between teachers' metacognition and learners’ higher-order thinking skills (HOTs). The correlational research method was employed to satisfy the investigation's primary objective. Two respondents were involved, including a total enumeration of Grade VI teachers and randomly selected Grade VI learners in Can-avid District. Through the administration of adapted sets of questionnaires and analysis of data using appropriate descriptive and inferential statistical tools, the study revealed the following salient findings: (1) majority of the teacher respondents indicated a very high level of conceptual knowledge of cognition and planning skills of cognition regulation rather than procedural knowledge and evaluating and monitoring skills; (2) learners have exhibited very poor higher-order thinking skills in terms of scientific inquiry skills of analyzing, evaluating, and creating; and that (3) teachers’ metacognition only manifested a weak negative correlation with learners creating skills. The study recommends the advancement of teachers’ metacognition and learners’ HOTs through active integration of said skills in the curriculum and providing opportunities for teachers’ professional advancement. Finally, future researchers should conduct a larger-scale inquiry to fully comprehend the relationship between the variables studied in this study and to fully realize the impact of metacognition on learners' skills, which was not demonstrated in this paper.